Democracy and Legitimacy in the European Union Revisited: Input, Output and 'Throughput'. (March 2013) - Schmidt, Vivien A.
Scholars of the European Union have analyzed the EU's legitimacy mainly in terms of two normative criteria: output effectiveness for the people and input participation by the people. This article argues that missing from this theorization is what goes on in the 'black box' of governance between input and output, or 'throughput'. Throughput consists of governance processes with the people, analyzed in terms of their efficacy, accountability, transparency, inclusiveness and openness to interest consultation. This article defines and discusses this third normative criterion as well as the interaction effects of all three normative criteria. It does so by considering EU scholars' institutional and constructivist analyses of EU legitimacy as well as empirical cases of and proposed solutions to the EU's democracy problems. The article also suggests that unlike input and output, which affect public perceptions of legitimacy both when they are increased or decreased, throughput tends to be most salient when negative, because oppressive, incompetent, corrupt or biased practices throw not just throughput but also input and output into question.